Enforcing Voluntary Compliance: The Need to Strengthen Hong Kong’s Merger and Acquisition Regulations - McMurtray, Nathan N. (Columbia Journal of Asian Law, 1998)
For many years commentators on merger and acquisition activities have noted that “the Pacific Rim has been and will become increasingly important.” Although several countries in the region are developing internal markets for these transactions, Hong Kong stands out in terms of size, volume and sophistication? Recently it has outpaced other regional markets and accounts for nearly one-third of the market share in Asia for these transactions (excluding Japan). Despite the recent financial turmoil throughout much of Asia, there remains reason to believe that the Hong Kong merger and acquisitions market will continue to grow. As China further liberalizes its economic policies and especially since Hong Kong has reverted to Chinese sovereignty, many mainland firms are looking overseas and commencing operations in Hong Kong. This is creating many potential new acquirers, targets, and increasing number of formerly rare transactions such as hostile takeovers and leveraged buyouts. Yet these changes also have the potential to slow or halt the development of this important financial market segment if not appropriately regulated. Perhaps reflecting this, Hong Kong’s Securities and Futures Commission recently announced that it would review the Hong Kong Code on Mergers and Takeovers (the “Code”) for the first time since 1992. Although the modifications discussed thus far by the Commission are limited in scope, a broad-based review and revamping of the regulatory system could be beneficial and bring the regulation of merger activity into closer harmony with the dramatic differences in the business and political environment since the Code was first put in place.